Distorting Electrical Power of the Alternating Current in the Simplest Circuit with a Diode - O. V. Bialobrzheskyi; D. Y. Rod`kin (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The development of electric power industry is accompanied by an increase in the number of consumers subjected to loads with nonlinear characteristics. The arising problem of the distortion of electrical energy that takes place when the mentioned consumers are in operation is partially solved by using means of improving the quality of electrical energy. The increase in the share of small generating plants that are placed in the nodes of consumers exacerbates the interaction of non-linear loads, forming additional parallel streams of electrical energy. Distorted electrical power is not an indication to account. Existing views on distorting power are amenable to criticism. In the well-known works, the proposals for the assessment of power using the quadratic norm and the quadratic norms of its components have been grounded. For the analysis of processes of formation the components of electrical power, a diagram of the simplest circuit containing a series-connected source of electromotive force, resistors and a diode is considered; also, the circuit was conditionally separated into a source and a consumer. The analysis of the power formation of each circuit element is performed with the use of the expression of current and voltage, as periodic functions represented by the trigonometric form of Fourier series. The power components are separated with the use of the known interaction of harmonic components of current and voltage of different orders. For the circuit elements, the power components formed by current and voltage harmonics of the same order are selected as well as power components formed by current and voltage harmonics of different orders, in which, in their turn, the power components are selected that have the same order as the first ones. The power formed by the action of the latter group is proposed to be attributed to the distorting power and to account its action by the corresponding quadratic norm. A numerical calculation has been performed with a use of the specified power component distribution. Time diagrams illustrate the process of interaction of the power components, which–in the case of the diode–leads to no change in power over time.